Tatiana Goricheva’s Ecotheology and Zootheology in the Formation of Affirmative Attitudes - Małek, Krzysztof (Poznańskie Studia Slawistyczne, 2024)
The purpose of the research was to identify the possibility of forming pro-animal and pro-ecological attitudes in Christians through the zootheological and ecotheological works of Tatiana Goricheva. The method of analysis and criticism of the literature was used, which supports the use of knowledge that has been analyzed, evaluated and synthesized through this method. The analyzed texts were both interviews with Tatiana Goricheva and her publications. The possibility of forming affirmative attitudes toward the natural world, including animals, based on traditional Christian values is demonstrated. Changing attitudes to friendly towards ecological and more pro-animal positions does not require changing one’s faith or ceasing to practice it or abandoning part of the tradition. Instead, it requires at least a partial commitment on the part of believers and the work of clergy and others teaching in communities.